The Future of Water: Technology, Challenges, and Islamic Perspective - Fenfen Fenda Florena; Ferli Septi Irwansyah; Karman Karman (Perhimpunan Intelektual Muslim Indonesia, 2021)
In all parts of the world, water is rapidly becoming an emerging issue. Mature technologies had been established in the water treatment process to overcome the issue. However, the water treatment technology advance does not mean it is not faced with its issues. In fact, it still leaves many problems for humans due to both technical issues and management problems. Understanding the water treatment process's proper perspective is required to achieve sustainable and equitable development for Muslim countries. In the other hand, Islam endeavors comprehensive guidelines on all aspects of human life and manages water resources. This mini-review article will give a brief explanation of some excellent technologies of water treatment and challenges associated with the advancing control over their beneficiation. Therefore, an Islamic perspective will be addressed to emphasize how Islamic-based policy and management can take a leading solution to overcome the fundamental problem for the future of water for the benefit of human life.